Modelling Transport - Ortuzar S., Juan de Dios.; Willumsen, Luis G. (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2011)
'With this fourth edition, Modelling Transport has been fully updated and revised to retain its position as the market-leading text in the field of transport modelling. As with previous editions, each subject is approached as a modelling exercise with discussion of the roles of theory, data, model specification, estimation, validation and application. This edition features four significant content enhancements; a new chapter on modelling for private sector projects; a new chapter on activity-based modelling; a new section on dynamic assignment and micro-simulation; and sizeable updates to the disaggregate modelling and Stated Preference sections. It also tackles topical issues such as congestion charging, global warming and the role of GPS in travel time surveys'--Provided by publisher.
'This edition features four significant content enhancements; a new chapter on modelling for private sector projects; a new chapter on activity-based modelling;'--Provided by publisher.
Includes bibliographical references (page 551-579) and index.
Keywords: Transportation -- Mathematical models; Choice of transportation -- Mathematical models; Trip generation -- Mathematical models